Pengaruh Motivasi Belajar dan Minat Belajar Terhadap Hasil Belajar Mata Pelajaran Administrasi Sistem Jaringan melalui Kegiatan Praktikum pada Siswa Kelas XI TKJ 2 SMK N 11 Malang - Nur Sa'ida Kismurdiani; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
This research is based on learning activities were held face-to-face which were previously carried out remotely during the covid 19 pandemic so that practicum learning activities at vocational schools can be carried out again in schools. The purpose of this research is to know the influence of learning motivation and learning interest to study result of grade XI TKJ 2 students on practical Network System Administration subjects at SMKN 11 Malang after practicum activities can be carried out again at school. A quantitative approach with the type of ex-postfacto research is used as a reference approach. Questionnaires are used as a data collection tool to obtain information about learning motivation and interest in learning that are distributed via the Google Form link, while learning scores are obtained from the final grades of class XI TKJ 2 practicums. The samples in this study were students of Grade XI Computer Engineering Network 2 SMKN 11 Malang which amount 32 people. This study uses a saturated sample, meaning that all members of the population are used as samples, namely all students of class XI. TKJ 2 which amounted to 32 people. The results of this study show that motivation in learning had no effect on learning outcomes with significant value of 0.450 > 0.05. interest in learning had no effect on learning outcomes with a significant value of 0,074 > 0,05. Learning motivation and Learning interest had no effect on Learning outcomes with significant value of 0,177 >0,05.